PENERAPAN PARIWISATA HIJAU DI KEMENUH MONKEY RIVER,GIANYAR,BALI - Widiantara, Ida Bagus; Murni, Ni Gst Nym Suci; Oka, I Made Darma (Universitas Pendidikan Ganesha, 2025)
Kemenuh Monkey River is one of tourism destination that located in Sukawati district, Gianyar regency, Bali. It is a nature-based tourism destination rich in biodiversity and cultural heritage. The area is characterized by a pristine river ecosystem, the presence of long-tailed macaques (Macaca fascicularis), and local communities that maintain strong traditional and spiritual practices. However, increasing environmental pressure from tourism development highlights the urgent need for a shift toward sustainable practices through the implementation of green tourism. This study aims to analyze the implementation green tourism at Kemenuh Monkey River through a multidimensional framework encompassing environmental, social, cultural, and economic aspects. And also, to analyse the model of green tourism implementation at Kemenuh Monkey River. This study uses a descriptive qualitative design. Data were collected through observation, interviews, focus group discussions, and literature review. From the research results, it is known that efforts have been made to implement green tourism. The implementation of green tourism is also in line with the local wisdom of the community, Tri Hita Karana. The philosophy includes a harmonious relationship between humans and God (parahyangan), fellow humans (pawongan), and the natural environment (palemahan) which become strong foundation in forming a green tourism model rooted in local wisdom. Environmentally, the area requires integrated waste management and ecological conservation. Socially and culturally, community participation and the preservation of local wisdom are essential to ensure identity-based tourism development. The implementation of green tourism is also outlined in traditional regulations/awig-awig. Economically, green tourism has the potential to enhance local economic growth through employment opportunity, profit sharing to the village, and eco-friendly businesses and community based enterprises. Preliminary findings indicate that Kemenuh Monkey River holds significant potential to serve as a model for green tourism in Bali. Effective implementation requires cross sector collaboration to raise awareness among all stakeholders to implement green tourism in accordance with the tri hita karana philosophy